Effective Strategies In Utilizing Social Media As A Promotional Tool At Pt Yogyakarta Tugu Televisi - Silvia Mardilla; Anas Hidayat (Cita konsultindo, 2024)
This study examines effective strategies for Jogja TV, the first local television station in Yogyakarta, to leverage social media in expanding audience reach and strengthening brand awareness. The approach used in this study is a quantitative approach. The data collection technique was by distributing online questionnaires to 100 respondents who were the audience of Jogja TV using Google Form. The sampling technique used a non-probability sampling technique using the purposive sampling method which was then processed using SPSS version 22.0. This study analyzes how Jogja TV can optimize the use of social media to expand the reach of the audience and strengthen brand awareness. The implementation of the right social media strategy can significantly strengthen the brand on Jogja TV. The effectiveness of Jogja TV's social media was evaluated based on indicators of attention (3.03), interest (3.23), information search (3.34), action (3.79), and information sharing (3.12). Results show that a well-implemented social media strategy can significantly enhance Jogja TV's brand. The study recommends developing a dedicated social media team to optimize promotions and build a stronger brand image.